Pyogenic Liver Abscess Caused by Methicillin-Susceptible Staphylococcus aureus in a 21-Year-Old Male - Samuel Igbinedion; Meher S. Mavuram; Moheb Boktor; John Bienvenu (Case Reports in Hepatology)
Liver abscesses are the most common types of visceral abscesses. Pyogenic liver abscesses, a particular type of liver abscesses, are uncommonly encountered. We present a rare case of pyogenic liver abscess caused by methicillin-susceptible Staphylococcus aureus in a young man. A 21-year- old man presented from prison to the hospital with fever, nausea, vomiting, diarrhea, and abdominal pain for five days. Labs were significant for leukocytosis with predominant neutrophilia and elevated liver enzymes. CT abdomen with contrast revealed an 8.4 cm multiloculated right hepatic mass extending to the kidney. Patient was started on broad spectrum antibiotics, given septic presentation. Peripheral blood cultures returned positive for methicillin-susceptible Staphylococcus aureus (MSSA). The culture from percutaneous drainage also revealed MSSA. He received a total of four weeks of IV Nafcillin therapy along with drainage of his abscess via percutaneous catheter. Follow-up revealed clinical resolution. This case highlights the importance of obtaining an aspirate from the liver abscess to better guide treatment strategy. Clinicians must consider broadening antibiotic coverage to include gram-positive organisms if the patient presents with severe illness and risk factors for Staphylococcus aureus infections.